The impact of turbulence and turbine operating condition on the wakes of tidal turbines. (March 2021) - Ebdon, Tim; Allmark, Matthew J.; O'Doherty, Daphne M.; Mason-Jones, Allan; O'Doherty, Tim; Germain, Gregory; Gaurier, Benoit
Abstract: Before initiating a study on the interaction of multiple wakes, it is imperative that turbine wake hydrodynamics are studied in isolation. In this paper CFD computer simulations of downstream turbine wakes have been run using a scale-resolving hybrid turbulence model known as a detached eddy simulation. To allow validation of the CFD simulations the computer models were supported by flume measurements with a lab scale tidal stream turbine run at three tip-speed ratios and three turbulence conditions, varying both turbulence intensity and length-scale. From the study it was demonstrated that turbulence intensity has a significant impact on the wake development for both recovery and width. The turbulence length scales of between 0.25 and 1.0 rotor diameter did not have a significant impact on the wake. The turbine operating condition also had an impact on the resulting wakes. In the near wake, centreline velocity recovery was found to increase with increasing turbine thrust due to flow being diverted towards the turbine nacelle. For a volumetric averaged wake, greater power extraction was found to cause the greatest near-wake deficit. Wake width was found to increase with increasing tip-speed ratio (and therefore turbine thrust). Highlights: Wake widths and lengths for a tidal turbine using three different analysis metrics are presented. Three levels of turbulent conditions are presented using upstream grids. The impact of the turbine operating conditions, on the wake characteristics, are analysed. The impact of turbulence intensity and Integral length scales on the wake characteristics are analysed.